The Role of Metal-on-Metal Bearings in Total Hip Arthroplasty and Hip Resurfacing: Review Article. Issue 1 (February 2017) - Sands, David; Schemitsch, Emil H.
Background: The current role of metal-on-metal (MoM) bearings in hip arthroplasty remains controversial. The low wear offered by MoM bearings compared to metal-on-polyethylene and the possibility of a lower risk of dislocation with larger head sizes, encouraged a trend towards the re-introduction of the MoM bearing couple. However, recent evidence has shown that not all designs of the MoM bearing have been successful. Questions/Purposes: The purpose of this paper is to provide an update on the use of MoM bearings and address the following issues: (1) the reintroduction of metal-on-metal bearings in total hip arthroplasty, (2) the failure of metal-on-metal bearings in stemmed total hip arthroplasty, (3) the role of metal-on-metal hip resurfacing in modern orthopaedics and (4) metal-on-metal hip resurfacing versus total hip arthroplasty. Methods: A literature search strategy was conducted using various search terms in MEDLINE and Embase. The highest quality articles that met the inclusion criteria and best answered the topics of focus of this review were selected. Key search terms included 'metal-on-metal', 'total hip arthroplasty' and 'hip resurfacing'. Results: The initial search retrieved 1240 articles. Twenty-two articles were selected and used in the review. Conclusion: Metal-on-metal hip resurfacing is still a suitable treatment option in specific patient populations with the appropriate implant design and surgical skill, while stemmed metal-on-metal total hip arthroplasty should be avoided in all patient populations. Continued follow-up of patients undergoing metal-on-metal hip resurfacing is critical in order to further understand the long-term outcomes of these patients and why certain complications tend to occur with this procedure.